2017
DOI: 10.1111/pce.12922
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for flowering locus T‐encoding genes in interpreting environmental and internal cues affecting olive (Olea europaea L.) flower induction

Abstract: Olive (Olea europaea L.) inflorescences, formed in lateral buds, flower in spring. However, there is some debate regarding time of flower induction and inflorescence initiation. Olive juvenility and seasonality of flowering were altered by overexpressing genes encoding flowering locus T (FT). OeFT1 and OeFT2 caused early flowering under short days when expressed in Arabidopsis. Expression of OeFT1/2 in olive leaves and OeFT2 in buds increased in winter, while initiation of inflorescences occurred i n late wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
116
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(135 citation statements)
references
References 90 publications
14
116
1
4
Order By: Relevance
“…There are also examples such as Arabidopsis Gy‐0 accession that reacts similarly to Arabidopsis Col , the main laboratory accession, regarding hypocotyl elongation, but shows a delay in flowering time when grown at 28°C (Verhage et al ., ). High temperature also delays flowering in cauliflower ( Brassica oleraceae ) (Verhage et al ., ), rice flower bush (Halevy et al ., ), olive trees (Haberman et al ., ) and some orchids (Newton and Runkle, ). Flowering time retardation by warm ambient temperature, as well as low temperature induction of FT‐ like genes, have been also described in mandarin (Nishikawa et al ., ), chrysanthemum (Nakano et al ., ) and litchi (Ding et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…There are also examples such as Arabidopsis Gy‐0 accession that reacts similarly to Arabidopsis Col , the main laboratory accession, regarding hypocotyl elongation, but shows a delay in flowering time when grown at 28°C (Verhage et al ., ). High temperature also delays flowering in cauliflower ( Brassica oleraceae ) (Verhage et al ., ), rice flower bush (Halevy et al ., ), olive trees (Haberman et al ., ) and some orchids (Newton and Runkle, ). Flowering time retardation by warm ambient temperature, as well as low temperature induction of FT‐ like genes, have been also described in mandarin (Nishikawa et al ., ), chrysanthemum (Nakano et al ., ) and litchi (Ding et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This result could have been obtained due to using low-dose GA 3 ; thus, like in the experiment of El-Naby et al (2012), the effects of GA 3 changed with different doses. On the other hand, Haberman et al (2017) indicated that when potted trees were exposed to artificial cold treatments in early summer (June) or fall (September), inflorescence formation could occur before the winter season. They identified two FT-encoding genes in the olive genome and provided evidence of a dramatic increase in both genes during the winter or by artificial cold-temperature treatment in other seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 75 ppm GA 3 treatment on the first of December increased vegetative growth, improved fruit characteristics, and increased the oil percentage. Haberman et al (2017) indicated that olive juvenility and seasonality of flowering were altered by overexpressing genes that encode flowering locus T (FT). OeFT1 and OeFT2 caused early flowering under short days when they were expressed in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…Both genomes contain 23 diploid chromosomes and an estimated size between 1.38-1.48 GB of sequence (Cruz et al 2016;Unver et al 2017). The domesticated olive genome (sequenced approximately one year prior to the wild olive genome) has been used for gene identification (Haberman et al 2017), discovery of olive fruit development programs (D'Angeli and Altamura 2016), and to improve understanding of genome structure (Barghini et al 2017).…”
Section: Introductionmentioning
confidence: 99%